2007
DOI: 10.3390/ijerph2007040002
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in the Global Health Workforce: The Greatest Impediment to Health in Sub-Saharan Africa

Abstract: Health systems played a key role in the dramatic rise in global life expectancy that occurred during the 20th century, and have continued to contribute enormously to the improvement of the health of most of the world’s population. The health workforce is the backbone of each health system, the lubricant that facilitates the smooth implementation of health action for sustainable socio-economic development. It has been proved beyond reasonable doubt that the density of the health workforce is directly correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
359
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(389 citation statements)
references
References 7 publications
5
359
0
1
Order By: Relevance
“…Significant deficiencies in access to basic healthcare, let alone specialty care, exist in many areas. 1,2 In the 1980s, the human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) pandemic brought a bewildering twist to overburdened healthcare providers. At the end of 2007, 18.1% of adults aged 15-49 in South Africa were HIV infected.…”
Section: Introductionmentioning
confidence: 99%
“…Significant deficiencies in access to basic healthcare, let alone specialty care, exist in many areas. 1,2 In the 1980s, the human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) pandemic brought a bewildering twist to overburdened healthcare providers. At the end of 2007, 18.1% of adults aged 15-49 in South Africa were HIV infected.…”
Section: Introductionmentioning
confidence: 99%
“…3 In low and middle-income countries, one major problem in primary care services is the allocation of health work force mainly in urban areas; in addition, available health personnel has mixed skills, as well as scarce opportunities for continuing education to provide quality health care. 4 In some Latin America countries, this situation has a multifactorial origin influenced by the rigidity and imperfections of the health system in identifying the needs for continuous improvement. 5,6 Across the Mexican public health care system, primary care provides ~85% of outpatient care, which in the year 2013 amounted to ~280 million visits, 7 i.e.…”
Section: Strategy For Strengthening Primary Health Carementioning
confidence: 99%
“…The role of supportive supervision and mentoring in making task shifting effective has been emphasized by the World Health Organization [23]. Moreover, Tanzania, particularly Mtwara and Lindi Regions, may benefit by learning from Zambian experience [24,25]. Morris et al did a study in Zambia and reported that the Zambian Ministry of Health has strongly supported an integrated program of task-shifting among providers.…”
Section: Health Systems and Policy Research Issn 2254-9137mentioning
confidence: 99%